The Impacts of Work Motivation on Elementary School Teachers’ Performance - Mardianton, Mardianton; Nellitawati, Nellitawati; Widiawati, Widiawati (Indonesian Research Journal in Education |IRJE|, 2023)
This research aimed to determine the effect of work motivation on elementary school teachers' performance. The research method used was a quantitative method with correlational descriptive techniques. The research population was 258 students from 34 public elementary schools in the Lubuk Sikaping district, Pasaman Regency. The research sample was taken 30% of the total population, so the research sample totaled 77 students by the stratified proportional random sampling technique. The data collection technique used in this research was a Likert scale questionnaire consisting of 5 alternative answers. The data analysis technique used was product-moment correlation and simple linear regression analysis, which was analyzed using the SPSS Version 24 program. The results showed that work motivation had a significant effect on teacher performance (41.7%). The rest was affected by other variables. The implication of this research is the need to increase teacher work motivation so that teachers can have higher performance.